Effect of CeO2 - Fe2O3 coated SiO2 nanoparticles on the thermal stability and UV resistance of polyurethane films - Ngoc Nhiem Dao; Thi Ha Chi Nguyen; Trung Dung Doan; Ngoc Chuc Pham; Quang Bac Nguyen; Thi Lim Duong; Ngo Nghia Pham; Vu Ngoc Mai Nguyen; Dai Lam Tran (My University, 2021)
Effect of CeO2 - Fe2O3 coated SiO2 nanoparticles on the thermal stability and UV resistance of polyurethane films
Keywords: CeO2-Fe2O3/SiO2